Cultural Power, Musical Hybridity, and Symbolic Resistance: Negotiating Tradition at the 2025 Jakarta International Java Jazz Festival - Verly Montolalu Joshua (Advances In Social Humanities Research, 2026)
This article aims to analyse the cultural power, musical hybridity, and symbolic resistance emerging in performance practices at the Jakarta International Java Jazz Festival 2025, through the interaction between global music industry networks and local musical traditions that represent Indonesia's cultural identity. This study employs a qualitative approach using document analysis and media discourse analysis of festival programmes, media reports, and promotional materials. The results show that cultural power is reflected in the curatorial structure, which places international artists at the centre of visibility, thereby shaping the symbolic hierarchy and aesthetic standards of performance. Musical hybridity emerges through the integration of traditional instruments, local rhythmic and melodic adaptations, and cross-cultural collaborations between Indonesian and international musicians, resulting in new musical expressions. Symbolic resistance is manifested through local musicians' strategies of displaying cultural identity by means of symbols, language, and tradition-based musical exploration. The findings also point to inherent tensions, whereby traditional elements tend to be adapted to global musical structures, carrying the potential for a simplification of meaning. Nevertheless, festivals remain dynamic spaces that allow for cultural negotiation and the articulation of local identities within the global music industry landscape. This research contributes by positioning music festivals as arenas for the production of cultural meaning through performance practices, and expands the study of international music festivals in Southeast Asia from the perspectives of cultural power, hybridity, and symbolic resistance.